Electronically Guided Blind Stick - Shahrul Anuar, Muhd Izhar; Daud, Azam Idham (2016)
The ordinary blind stick is not completely assist blind people to walk in securely and there is still several problem that blind people have to face. For an example, blind people may hard to detect a wet or muddy terrain using the ordinary blind stick. The guide dogs that navigating their human comes with many disadvantages such as high cost and only suitable for about five years. To cover this disadvantages, this research has done to develop a blind stick with more safety features. Also the aim of this project is to show that this project technology can be used to provide safety for the blind people. Then, to design a combination of all circuit into one complex circuit connected to the PIC. This project is actually consists of two parts, hardware and software. Hardware refer to the development of the device itself including the circuit constructing, printed circuit board (PCB) etching and soldering process. As for the software, it is focused on the program development specifically during the simulation, compilation and PIC burning process. There are 3 sensor that produced a different input used in this project and each input will come with different output from another. The ultrasonic sensor will detect obstacles and the motor will vibrate as any obstacle detected. The LDR will detect the presence of darkness and the LED will be turn ON. The electrode will detect the wet or moisture and the buzzer will activated. This process is controlled and commanded by the PIC. Lastly, at the end of the project development, a few experiences are gained conducting research and construct the hardware of this project. Hopefully, the development of electronically guided walking blind stick has given many benefits toward a blind people.